2004
DOI: 10.1161/01.cir.0000109698.70638.2b
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Oxidant Stress Enhances Progression and Angiogenesis of Experimental Atheroma

Abstract: Background-Although multiple pathological processes have been associated with oxidative stress, the causative relation between oxidative stress and arterial lesion progression remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(140 citation statements)
references
References 35 publications
6
132
0
2
Order By: Relevance
“…For instance, overexpression of the NADPH oxidase subunit, p22 phox has been shown to increase HIF-1a, VEGF expression and intralesional angiogenesis and to promote experimental atheroma progression. 44 Our present data demonstrated that deficiency of the NADPH oxidase p47 phox attenuates Ang-2 expression and blunts angiogenic response in the neointima of DIO mice. Our data also show that leptin-induced Ang-2 expression, as well as cell migration and proliferation are dependent on NADPH oxidase.…”
Section: Disscussionsupporting
confidence: 60%
“…For instance, overexpression of the NADPH oxidase subunit, p22 phox has been shown to increase HIF-1a, VEGF expression and intralesional angiogenesis and to promote experimental atheroma progression. 44 Our present data demonstrated that deficiency of the NADPH oxidase p47 phox attenuates Ang-2 expression and blunts angiogenic response in the neointima of DIO mice. Our data also show that leptin-induced Ang-2 expression, as well as cell migration and proliferation are dependent on NADPH oxidase.…”
Section: Disscussionsupporting
confidence: 60%
“…In VSMC, therefore, insulin activates the HIF-1/VEGF pathway, which is deeply involved in new blood vessel formation [18], thus mimicking the action of hypoxia [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the combination of inactivation of NO • by O 2 •− and increased production of the endothelial hyperpolarizing factor H 2 O 2 leads to impaired vasodilation (Bauersachs et al 1996). The balance between endothelial proliferation and apoptosis is also altered by ROS, which can lead to excessive angiogenesis (Khatri et al 2004) or loss of endothelial cells (Lin et al 2004). All of these consequences contribute to the pathophysiology of the response to injury.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%